Perception of Teachers on The Need for Effective Integration of African Indigenous Knowledge in Nigeria’s Primary School Education - Blessing Chinonyerem Chiedozie (International Journal of Educational Review, 2026)
This study investigated the perception of teachers on the need for effective integration of Africa indigenous knowledge into Nigeria’s primary school education. The sample consisted of 400 teachers, 200 each from private primary schools and 200 from public primary schools, randomly selected from public and private primary schools in Lagos state. The instrument was a questionnaire validated by test retest method. The research design was the descriptive survey. Results showed that pupils are mostly introduced to folktales and English language used more than the native language (Ibo or Yoruba) in passing on information. Simple percentage and Chi-square were used to analyse perception of private primary school teachers and public primary school teachers on the need for effective integration of African Indigenous Knowledge (AIK) into primary school education. It was found that there was no significant difference in the perception of private primary school teachers and public primary school teachers on the need for effective integration of African Indigenous Knowledge into primary school formal education in Nigeria on the basis of school status. The results showed that respondents were unanimous in indicating that African Indigenous Knowledge be effectively integrated into formal primary school education system. The findings showed that most respondents agree to the statement that effective integration of African Indigenous Knowledge will promote our cultural heritage and National development in Nigeria. Major barriers or obstacles to effective integration were identified and suggestions on how to facilitate the effective integration of African Indigenous Knowledge into primary school education system were given.